Frontiers in hemodialysis part II: Toward personalized and optimized therapy. (August 2020) - Marano, Stefano; Marano, Marco; Pecchia, Leandro
Abstract: This article describes new protocols for intermittent hemodialysis, based on a mathematical model for bicarbonate restoring, which ameliorate drawbacks of the standard therapy and allow the nephrologist to design any desired profile of bicarbonate concentration in the patient blood, enabling a safer and more effective treatment. The proposed protocols can be tailored to patient-specific clinical prescriptions, opening the way to highly personalized hemodialysis treatments. This article describes a simpler and more insightful solutions to the same mathematical model considered in previous works, with more straightforward system-theory interpretation. This is relevant as it leads to self-explaining evidences of the underlying physiological mechanisms, which is crucial in order to communicate the model potential to clinicians, not necessarily skilled in advanced math modeling.